Evaluating the impact of a champion on implementation of the Back Skills Training (BeST) programme in Canada: a mixed methods feasibility study protocol. Issue 11 (30th November 2020) - Hall, Amanda; Richmond, Helen; Bursey, Krystal; Hansen, Zara; Williamson, Esther; Copsey, Bethan; Albury, Charlotte; Asghari, Shabnam; Curran, Vernon; Pike, Andrea; Etchegary, Holly; Lamb, Sarah
Abstract : Introduction: There is global recognition that low back pain (LBP) should be managed with a biopsychosocial approach. Previous implementation of this approach resulted in low uptake and highlighted the need for ongoing support. This study aims to explore the feasibility of (i) training and using a champion to support implementation, (ii) using a cluster randomised controlled trial (RCT), (iii) collecting patient reported outcome measures in a Canadian public healthcare setting and to identify contextual barriers to implementation. Methods: A pragmatic cluster RCT with embedded qualitative study with physiotherapists treating LBP in publicly funded physiotherapy departments in Newfoundland and Labrador, Canada. Participants will complete a previously developed online training course to equip them to deliver a biopsychosocial intervention for LBP. Clusters randomised to the intervention arm will receive additional support from a champion. A minimum champion training package has been developed based on known barriers in the literature. This includes strategies to target barriers relating to group-based scheduling issues, lack of managerial support, perceived patient factors such as addressing patient expectations for other types of treatments or selecting which patients might be best suited for this intervention, and anxiety about delivering something new. This package will be further codeveloped with study champions based on identified implementation barriers using the Behaviour Change Wheel. Clusters will be monitored for 6 months to assess champion and physiotherapist recruitment and retention, acceptability and implementation of the champion training, and the viability of conducting a cluster RCT in this setting. A purposive sample of physiotherapists will be interviewed from both arms. Ethics and dissemination: This study was approved by Newfoundland and Labrador Health Research Ethics Authority in December 2018. Results will be disseminated to academic audiences through conferences and peer reviewed publications; to all study participants, their clinical leads, and patients with LBP. Trial registration number: ClinicalTrials.gov Identifier: NCT04377529 ; Memorial University of Newfoundland Protocol Record 20190025; Pre-results.